2002
DOI: 10.1016/s1570-0232(02)00557-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary analysis of nephrolithiasis markers

Abstract: Renal stone disease is an ancient and common affliction, common in industrialised nations. The causes and incidence of nephrolithiasis are presented. Afterwards, the promoters and inhibitors of renal stone formation analysis in urine are described including enzymatic methods, chromatography, capillary electrophoresis and other techniques. Aspects such as sample collection and storage are also included. The review article includes referenced tables that provide summaries of methodology for the analysis of nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 123 publications
(65 reference statements)
1
53
0
2
Order By: Relevance
“…This suggests that alkaline urine tends to precipitate magnesium, which may complex with ammonium and phosphate excreted in urine. Treatment with aqueous extract of Melia azadirachta reduced the pH values to 6.5−7.5 supporting the decrease in stone weight and urinary excretion of stone forming ions in antiurolithiatic study, indicating the influence of the extract in dissolving urinary calculi [17]. All this supports the effectiveness of the aqueous extract of Melia azadirachta against prevention of stone formation and its ability to dissolve preformed stones.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…This suggests that alkaline urine tends to precipitate magnesium, which may complex with ammonium and phosphate excreted in urine. Treatment with aqueous extract of Melia azadirachta reduced the pH values to 6.5−7.5 supporting the decrease in stone weight and urinary excretion of stone forming ions in antiurolithiatic study, indicating the influence of the extract in dissolving urinary calculi [17]. All this supports the effectiveness of the aqueous extract of Melia azadirachta against prevention of stone formation and its ability to dissolve preformed stones.…”
Section: Discussionsupporting
confidence: 63%
“…Quantitative analysis of the stones based on surface and weight indicated that the large stones formed were of magnesium ammonium phosphate (struvite) type with traces of calcium and oxalate [17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations